Green Deal in Focus: Regional Perspectives and Their Influence on Electoral Income - Melania- Gabriela CIOT; Cristina-Matilda VĂNOAGĂ; Luciana-Mirela BUTIȘCĂ (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
European Green Deal policies and strategies has sparked vivid debate in the European Parliament in the last EP mandate, especially after a row of world-wide and regional crises, such as COVID-19, the Russian invasion of Ukraine and high energy prices. There was registered disagreement in terms of fulfilling the EGD desiderates at a fast pace. If the Greens have lately received less support, the far-right, very vocal when it comes to Green Deal strategies and legislation, seems to be more appalling to voters throughout Europe. The 2024 EP elections were to a discourse level a mirror for all the above-mentioned aspects. Our article analyzes if EGD themes are present in the electoral programs of the main parties and independent EP parties/ independent candidates in Romania and if they are also present in the electoral discourses reflected on the main media platforms during the campaign.